Attentional set-shifting and social abilities in children with schizotypal and comorbid autism spectrum disorders. (January 2018) - Abu-Akel, Ahmad; Testa, Renee R; Jones, Harvey P; Ross, Nola; Skafidas, Efstratios; Tonge, Bruce; Pantelis, Christos
Objective: While diagnostically independent, autism and schizotypal disorders can co-occur. Their concurrent impact on outcomes and phenotypes has not been investigated. We investigated the impact of comorbid autism and schizotypal disorders in children on executive functioning and socio-pragmatic skills – core features of both disorders. Method: Executive functioning (assessed with the Cambridge Neuropsychological Test Automated Battery ) and socio-pragmatic skills (assessed using the Melbourne Assessment of Schizotypy in Kids ) were investigated in a total of 67 (6–12 year old) children with autism ( n = 15; M/F = 10/5), schizotypal disorder ( n = 8; M/F = 5/3) and comorbid autism and schizotypal disorder ( n = 12; M/F = 5/7) and typically developing children ( n = 32; M/F = 17/15). Results: Both the autism and schizotypal disorder groups performed more poorly than the typically developing group on socio-pragmatic skills and overall performance (i.e. number of stages completed) of the intra-/extra-dimensional set-shifting task (all p s < 0.001). Clear distinctions between the autism and schizotypal groups were present in the intra-/extra-dimensional task relative to the typically developing group – the autism group had difficulties with extra-dimensional shifts ( p < 0.001), and the schizotypal disorder group with intra-dimensional shifts ( p = 0.08). Interestingly, the overall performance of the comorbid group on the intra-/extra-dimensional task was not significantly different from the typically developing group, and they were superior to both the autism ( p = 0.019) and schizotypal disorder ( p = 0.042) groups on socio-pragmatic skills. Conclusion: The phenotypical overlap between autism and schizotypal disorders may be precipitated by different cognitive styles and/or mechanisms associated with attention and information processing. We propose that sustaining and switching attention represent two poles of irregularities across the autism and schizotypal spectra, which appear to converge in a compensatory manner in the comorbid group. Our findings highlight the importance of investigating children with a dual diagnosis of autism and schizotypal disorders, and raise intriguing questions about possible mechanisms to explain the attenuated impairment observed in the group of children with comorbid autism and schizotpyal disorders.